miRNA in Circulating Microvesicles as Biomarkers for Age-Related Cognitive Decline - Rani, Asha; O’Shea, Andrew; Ianov, Lara; Cohen, Ronald A.; Woods, Adam J.; Foster, Thomas C. (Frontiers in Aging Neuroscience, 2017)
Community dwelling older individuals from the North Florida region were examined for health status and a comprehensive neuropsychological battery, including the Montreal Cognitive Assessment (MoCA), was performed on each participant. A subpopulation (58 females and 39 males) met the criteria for age (60-89) and no evidence of mild cognitive impairment, with a MoCA score ≥ 23. Despite the stringent criteria for participation, MoCA scores were negatively correlated within the limited age range. Extracellular microvesicles were isolated from the plasma and samples were found to be positive for the exosome marker CD63, with an enrichment of particles within the size range for exosomes. miRNA was extracted and examined using next generation sequencing with a stringent criterion (average of ≥ 10 counts per million reads) resulting in 117 miRNA for subsequent analysis. Characterization of expression confirmed pervious work concerning the relative abundance and overall pattern of expression of miRNA in plasma. Correlation analysis indicated that most of the miRNAs (74 miRNAs) were positively correlated with age (p < 0.01). Multiple regression was employed to identify the relationship of miRNA expression and MoCA score, accounting for age. MoCA scores were negatively correlated with 13 miRNAs. The pattern of expression for cognition-related miRNA did not match that previously described for Alzheimer’s disease. Enrichment analysis was employed to identify miRNA-gene interactions to reveal possible links to brain function.